″A Method of Developing Communicative Competence of Future Teachers of Technical Subjects″. - Kalinichenko, T. (Problems of Engineer-Pedagogical Education, 2018)
The article considers the issue of devising a method for developing communicative competence of future teachers of technical disciplines. The suggested method allows complex development of motivational, value-oriented, cognitive, activity-based, and personality components of communicative competence of future teachers of technical subjects. The method of forming communicative competence is founded on the stages of mastering professional activities and envisages feedback at all stages of the development of communicative competence. The author presents a graphic image of the model of the method of acquiring communicative competence. The paper provides a detailed description of every stage of the method and describes the sequence of their implementation. The suggested method for developing communicative competence will be applied during lectures, practical sessions and independent work of future teachers of technical subjects.